2020
DOI: 10.1111/ssm.12382
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the state of science stereotypes: Systematic review and meta‐analysis of the Draw‐A‐Scientist Checklist

Abstract: This systematic review and meta-analysis examined recent articles that have used the 1995 Draw-A-Scientist Checklist (DAST-C). This study was focused on the current state of students' stereotypes of scientists and the appropriateness of the DAST-C as a tool to assess these perceptions. Articles included in the review were published between 2003 and 2018, resulting in n = 30 studies. Mean results across studies are presented to describe current stereotypes of scientists, and the current format of the DAST-C is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 43 publications
1
26
0
1
Order By: Relevance
“…It is worth to note that symbols of research (e.g., specimens and equipment) were more observed more often than symbols of knowledge (e.g., computers and notebooks), which is a common finding among most DAST-based research (Ferguson & Lezotte, 2020) Frequency counts, of the demographic attributes of scientists that were coded varied greatly across textbook publishers. Research by Good et al (2010) found that texts that contained non-stereotypical images of scientists (women scientists) improved female students comprehension of said text when compared to reading the same texts with stereotypical imagery (male scientists).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is worth to note that symbols of research (e.g., specimens and equipment) were more observed more often than symbols of knowledge (e.g., computers and notebooks), which is a common finding among most DAST-based research (Ferguson & Lezotte, 2020) Frequency counts, of the demographic attributes of scientists that were coded varied greatly across textbook publishers. Research by Good et al (2010) found that texts that contained non-stereotypical images of scientists (women scientists) improved female students comprehension of said text when compared to reading the same texts with stereotypical imagery (male scientists).…”
Section: Discussionmentioning
confidence: 98%
“…For children and adolescent learners, images play in influential role in their perceptions of scientists, which have evidenced by the plethora of research exploring scientists in film (Steinke, 2005), the media (Steinke et al, 2006(Steinke et al, , 2007(Steinke et al, , 2009, television (Steinke et al, 2008), trade books (Finson et al, 2017;Ford, 2006), and on the internet (Fujiwara et al, 2021). Thus, the exploration of students' perceptions of science and scientists is not a new endeavor, starting with early research by Mead and Metraux (1957), continuing to present day (e.g., Ferguson & Lezotte, 2020) and expanding internationally (e.g., Chionas & Emvalotis, 2021). A common and coherent strategy to both elicit and understand students' perceptions of a scientist is the Draw a Scientist Test (DAST; Chambers, 1983) and checklist (DAST-C) (Finson et al, 1995), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The universality of students' perceptions suggests that common influences, like western media, may be contributing to students' perceptions of science and scientists worldwide (Finson, 2003;Steinke et al, 2007;Jones & Hite, 2020). In their meta-analysis of DAST studies, Ferguson and Lezotte (2020) recommended revisions to DAST coding and analysis to better capture students' stereotypes so researchers may better understand from which these perceptions are sourced and their implications in perceptions of science in their future lives. This study connected career consideration using a novel approach (via C&C theory) to DAST data as a step in the direction toward expanding the DAST as a tool for researching science perceptions and career aspirations across the K-12 continuum.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, different modifications were made to this test by different researchers [36]. This test, DAST, and its versions modified by other researchers, have been the most widely used tools for the analysis of drawings made by students in recent decades [6,28,37].…”
Section: Introductionmentioning
confidence: 99%